Pendampingan Adaptasi dan Adopsi Common European Framework For Languages (CEFR) ke Kurikulum Bahasa Inggris di SDN Model Mataram - Farmasari, Santi; Susanti, Ni Wayan Mira; Wardana, Lalu Ali; Suryaningsih, Hartati; Herayana, Desi (Universitas Mataram, 2024)
This community service was conducted to assist the English teachers at Sekolah Dasar Negeri Model Mataram (SDNMM) adapt and adopt the Common European Framework (CEFR) for Languages into the English Curriculum of the school. The activity involved all English teachers at the school (11 teachers) and the assistance was conducted for one week. The adaptation and adoption processes were completed in four stages: (1) mapping out the core competencies of the CEFR for English primary and the core competences of the SDNMM English curriculum, (2) aligning the core competences of English in the school curriculum, (3) modifying the SDNMM English Curriculum. Some factors which inform the reducement and addition of the competences include (1) the students’ existing competencies, (2) teachers’ teaching competencies, (3) the available reseources at the school, and (4) the school vision and mission.